- #1

e^(x+3) = pi^x

I got these results, but I'm not sure if it is correct:

ln^(x+3) = ln(pi^x)

(x+3)ln = xln(pi)

xln + 3ln = xln(pi)

3ln = xln(pi)-xln

3ln = x(ln(pi) - ln)

x = 3ln/ln(pi)-ln

NOTE: PI =3.14 (I don't know how to insert the symbol pi)

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter jaypee
- Start date

- #1

e^(x+3) = pi^x

I got these results, but I'm not sure if it is correct:

ln^(x+3) = ln(pi^x)

(x+3)ln = xln(pi)

xln + 3ln = xln(pi)

3ln = xln(pi)-xln

3ln = x(ln(pi) - ln)

x = 3ln/ln(pi)-ln

NOTE: PI =3.14 (I don't know how to insert the symbol pi)

- #2

ln(e)=1

and you should be able to get it from there...

- #3

chroot

Staff Emeritus

Science Advisor

Gold Member

- 10,275

- 40

Step 1. Take the natural logarithm of both sides of the equation:

ln(e^(x+3)) = ln(pi^x)

this becomes

x+3 = x * ln(pi)

Step 2. Isolate x on one side of the equation

3 = x * ln(pi) - x

3 = x (ln(pi) - 1)

Step 3. Solve for x

x = 3 / (ln(pi) - 1)

- Warren

- #4

camel2

- 1

- 0

I'm having difficulty in solving for x,in the equation e^x=4-x^2

help please

lne^x=ln(4-x^2)

x=ln(4-x^2) and this is as far as iI got

help please

lne^x=ln(4-x^2)

x=ln(4-x^2) and this is as far as iI got

Last edited:

Share:

- Last Post

- Replies
- 2

- Views
- 386

- Last Post

- Replies
- 3

- Views
- 380

- Last Post

- Replies
- 3

- Views
- 470

- Last Post

- Replies
- 3

- Views
- 380

- Last Post

- Replies
- 1

- Views
- 262

- Replies
- 46

- Views
- 1K

- Last Post

- Replies
- 22

- Views
- 871

MHB
Question help

- Last Post

- Replies
- 0

- Views
- 396

- Last Post

- Replies
- 4

- Views
- 462

- Last Post

- Replies
- 5

- Views
- 813